Carbon Nanomaterials Interfacing with Neurons: An In vivo Perspective - Baldrighi, Michele; Trusel, Massimo; Tonini, Raffaella; Giordani, Silvia (Frontiers in Neuroscience, 2016)
Developing new tools that outperform current state of the art technologies for imaging, drug delivery or electrical sensing in neuronal tissues is one of the great challenges in neurosciences. Investigations into the potential use of carbon nanomaterials for such applications started about two decades ago. Since then, numerous in vitro studies have examined interactions between these nanomaterials and neurons, either by evaluating their compatibility, as vectors for drug delivery, or for their potential use in electric activity sensing and manipulation. The results obtained indicate that carbon nanomaterials may be suitable for medical therapies. However, a relatively small number of in vivo studies have been carried out to date. In order to facilitate the transformation of carbon nanomaterial into practical neurobiomedical applications, it is essential to identify and highlight in the existing literature the strengths and weakness that different carbon nanomaterials have displayed when probed in vivo. Unfortunately the current literature is sometimes conflicting and confusing. To offer a clearer picture of the in vivo studies on carbon nanomaterials in the central nervous system, we provide a systematic and critical review. Hereby we identify properties and behavior of carbon nanomaterials in neural tissue, and we examine key achievements and potentially problematic toxicological issues.